A Decade After the Global Recession : Lessons and Challenges for Emerging and Developing Economies - Kose, M. Ayhan; Ohnsorge, Franziska (Washington, DC: World Bank, 2019)
This year marks the tenth anniversary of the 2009 global recession. Most emerging market and developing economies weathered the global recession relatively well. However, following a short-lived initial rebound in activity in 2010, the global economy and, especially, emerging market and developing economies, have suffered a decade of weak growth despite unprecedented monetary policy accommodation and several rounds of fiscal stimulus in major economies. A Decade After the Global Recession provides the first comprehensive stock-taking of the decade since the global recession for emerging market and developing economies. It reviews the experience of emerging market and developing economies during and after the recession. Many of these economies have now become more vulnerable to economic shocks. The study discusses lessons from the global recession and policy options for these economies to strengthen growth and be prepared should another global downturn occur.